Method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron
By modifying nano-ferrous activate sodium persulfate, the nano-ferrous material is coated with ginkgo leaf extract and carboxymethyl cellulose, combined with oscillation reactions of specific temperature and pH conditions, the high cost and long-term PCBs repair process in soil is solved. The cycle problem has achieved efficient and environmentally friendly PCB118 degradation, which is suitable for a wide range of PCBs-contaminated soil repair.
Patent Information
- Application Number
- CN202411696796.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art has problems such as high cost, long repair cycle, complex process and secondary pollution in the process of PCBs repair in soil, and it is particularly difficult to effectively degrade hyperchlorobenzene.
Modified nano-ferrous iron is used to activate sodium persulfate by coating the ginkgo leaf extract and carboxymethyl cellulose. The modified nano-ferrous material is prepared by combining the oscillation reaction of sodium persulfate at different temperatures and pH conditions to improve the sulfate root The generation and reactivity of free radicals achieve efficient degradation of PCB118.
The efficient degradation rate of PCB118 in the soil is achieved, with a degradation rate of up to 68.7% to 70.5%, which simplifies equipment and operations, avoids secondary environmental pollution, and is suitable for the restoration of soil contaminated by PCBs of 209 homologs.
Smart Images

Figure CN119281809A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental chemistry, and in particular relates to a method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron. Background Art
[0002] Polychlorinated biphenyls (PCBs) are chlorinated aromatic hydrocarbons, which are formed by arbitrarily replacing the 10 hydrogen atoms on the biphenyl ring with chlorine atoms. According to the different positions and numbers of chlorine atoms, there are theoretically 209 homologues of PCBs, with the general molecular formula of C 12 H 10-n Cl n (where n represents the number of chlorine atoms in the molecule). Generally, according to the degree of chlorination, monochlorine to tetrachlorine are called low-chlorinated biphenyls, and pentachlorine to decachlorine are called high-chlorinated biphenyls. As the number of chlorine atoms increases, the stability of PCBs increases, and the half-life also increases. PCBs are a kind of bactericidal, highly toxic organic pollutants with extremely strong stability and difficult to degrade. However, due to the good insulation properties and chemical stability of PCBs, they were widely used in industrial products such as electrical equipment, thermal conductors and flame retardants in the past. my country began to produce PCBs in 1965 and stopped production in the early 1980s. The cumulative output was nearly 10,000 tons, of which pentachlorinated biphenyl accounted for about 1,000 tons. In the long-term production and use of polychlorinated biphenyls, certain pollution has been caused to the atmosphere, water bodies, and soil environment. Its significant fat solubility makes PCBs very easy to combine with organic matter in the soil, causing it to deposit and exist in the soil for a long time. Therefore, soil has become the main destination of polychlorinated biphenyls in the environment, and the pollution remediation of polychlorinated biphenyls in the soil has attracted much attention.
[0003] There are many methods for remediating PCBs in soil, but traditional remediation technologies have some limitations in application, such as high remediation cost, long remediation cycle, and secondary pollution. Therefore, with the further development and application of remediation technology, some new advanced oxidation technologies have been rapidly developed. Among them, sulfate free radical (SO 4 ·- ) is a kind of advanced oxidation technology that has developed rapidly in recent years. This method mainly uses persulfate to ionize in water to produce persulfate ions (S 2 O 8 2- ), S 2 O 8 2- It is a kind of oxidant with strong oxidizing ability. In the presence of light, heat, transition metal ions, etc., S 2 O 8 2- The peroxy group (OO) in S 2 O 82- Activated into sulfate radical. SO 4 ·- The standard redox potential of SO is 2.6V, which is higher than that of most organic matter, so it can degrade most organic pollutants. 4 ·- It can react with water to form another strong oxidant ·OH, whose redox potential is 2.7V. Organic pollutants can be quickly converted into harmless small molecules such as carbon dioxide in the environment. 4 ·- Applicable to a wide pH range. Therefore, the advanced oxidation technology of persulfate has shown obvious superiority in the field of treating difficult-to-degrade organic pollutants. It is widely used to treat difficult-to-degrade persistent organic pollutants such as polycyclic aromatic hydrocarbons and PCBs. It is also an environmentally friendly technology used in soil remediation.
[0004] Persulfate is relatively stable at room temperature and has a weak direct degradation effect on organic pollutants. Activation can break the OO bond in the persulfate molecule to generate SO with a higher redox potential. 4 ·- , improve the reactivity of persulfate, so that it can more effectively degrade the target pollutants. Currently, the commonly used methods for activating persulfate include transition metal activation, light activation, alkali activation and thermal activation. Among them, nano-iron has a large specific surface area, high reactivity, good degradation effect on pollutants, simple operation process, and no need for external energy input. It is a more commonly used method for activating persulfate.
[0005] In order to effectively remove PCBs from soil, scholars have proposed various remediation methods, which are mainly divided into physical remediation, chemical remediation and biological remediation. Physical remediation methods have problems such as inability to achieve complete degradation of PCBs and high cost. Traditional chemical remediation methods have problems such as complex process flow and high treatment costs. Biological remediation methods have the disadvantages of being only applicable to low-concentration contaminated soils, long remediation time and long microbial culture cycle. These factors limit the further development and application of these existing traditional remediation technologies. Summary of the invention
[0006] The purpose of the present invention is to provide a method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron, so as to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron comprises the following steps:
[0009] Step 1: Preparation of contaminated soil samples: Grind the collected farmland soil without PCBs contamination through a 0.25 mm sieve, add the PCB118 standard solution dissolved in acetone solution to the soil sample, soak it in acetone solution, stir it and place it in a fume hood to dry, and store it for later use. The initial concentration of PCB118 is 9.1 mg / L;
[0010] Step 2: Preparation of plant extract: Use ginkgo leaves, which are common in both northern and southern my country, to prepare plant extract. Wash the ginkgo leaves with deionized water, air-dry, grind through a 0.25 mm sieve, heat in a water bath at 80°C for 1 h at a concentration ratio of ginkgo leaf powder / deionized water of 36 g / 600 mL, cool to room temperature, and then vacuum filter. The filtrate is the ginkgo leaf extract.
[0011] Step 3: Preparation of environmentally friendly modified nano-iron: 150 mL of 0.5% carboxymethyl cellulose solution was added dropwise to 150 mL of 0.2 mol / L FeCl 3 6H 2 O solution, stirred for 20 minutes, then the prepared ginkgo leaf extract was added dropwise to the mixed solution, stirred, reacted for 30 minutes, the obtained black suspension was centrifuged at a speed of 8000r / min for 10 minutes, the supernatant was discarded, washed with anhydrous ethanol 3 times, washed with deionized water 3 times, and freeze-dried for 24 hours to obtain a carboxymethyl cellulose-nano iron composite material (CMC@G-nZVI);
[0012] Step 4: Establishment of the PCB118 degradation reaction method in soil: Weigh 2 g of PCB118-contaminated soil and place it in a conical flask, add CMC@G-nZVI composite material to the conical flask, then add 2 mL of deionized water and 2 mL of PS solution, adjust the initial pH value of the solution, seal it, and oscillate (speed of 160 r / min) under different temperature conditions for 24 hours. After sampling, immediately add 0.2 mL of methanol to stop the reaction.
[0013] Preferably, the CMC@G-nZVI composite material added in the step four includes but is not limited to 0.002g, 0.02g, 0.2g, the concentration of the PS solution in the step four includes but is not limited to 0, 0.05, 0.15, 0.25, 0.35 mol / L, the initial pH value of the solution in the step four includes but is not limited to 3, 5, 7, 9, and the temperature during oscillation under the different temperature conditions includes but is not limited to 15, 25, 35, 45°C.
[0014] Preferably, the following steps are also included: adding 0.02 g of CMC@G-nZVI composite material, 2 mL of deionized water and 2 mL of 0.35 mol / L PS solution to 2 g of PCB118 contaminated soil, adjusting the initial pH of the solution to 3, and oscillating (at a speed of 160 r / min) for 24 h under the conditions of a reaction temperature of 45°C.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The present invention uses environmentally friendly experimental materials, uses plant extracts to prepare nano iron through a green synthesis method, uses carboxymethyl cellulose to coat and prepare modified nano iron materials, and establishes reaction conditions and methods for the modified nano iron materials to activate sodium persulfate to degrade PCB118 in soil. The inventive method is suitable for the remediation of PCBs-contaminated soil with 209 homologues. Compared with other methods, this method can treat high-chlorinated biphenyls and low-chlorinated biphenyls, and the concentration range of the treated pollutants is wide. It has the advantages of simple preparation and treatment methods, simple required equipment, and no secondary pollution to the environment. It is easy to promote and use and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figure is a flow chart of the method for degrading PCB118 in soil according to the present invention. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Embodiment 1:
[0020] See also Figure 1 As shown, a method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron comprises the following steps:
[0021] Step 1: Preparation of contaminated soil samples: Grind the collected farmland soil without PCBs contamination through a 0.25 mm sieve, add the PCB118 standard solution dissolved in acetone solution to the soil sample, soak it in acetone solution, stir it and place it in a fume hood to dry, and store it for later use. The initial concentration of PCB118 is 9.1 mg / L;
[0022] Step 2: Preparation of plant extract: Use ginkgo leaves, which are common in both northern and southern my country, to prepare plant extract. Wash the ginkgo leaves with deionized water, air-dry, grind through a 0.25 mm sieve, heat in a water bath at 80°C for 1 h at a concentration ratio of ginkgo leaf powder / deionized water of 36 g / 600 mL, cool to room temperature, and then vacuum filter. The filtrate is the ginkgo leaf extract.
[0023] Step 3: Preparation of environmentally friendly modified nano-iron: 150 mL of 0.5% carboxymethyl cellulose solution was added dropwise to 150 mL of 0.2 mol / L FeCl 3 6H 2 O solution, stirred for 20 minutes, then the prepared ginkgo leaf extract was added dropwise to the mixed solution, stirred, reacted for 30 minutes, the obtained black suspension was centrifuged at a speed of 8000r / min for 10 minutes, the supernatant was discarded, washed with anhydrous ethanol 3 times, washed with deionized water 3 times, and freeze-dried for 24 hours to obtain a carboxymethyl cellulose-nano iron composite material (CMC@G-nZVI);
[0024] Step 4: Establishment of the PCB118 degradation reaction method in soil: Weigh 2 g of PCB118-contaminated soil and place it in a conical flask, add CMC@G-nZVI composite material to the conical flask, then add 2 mL of deionized water and 2 mL of PS solution, adjust the initial pH value of the solution, seal it, and oscillate (speed of 160 r / min) under different temperature conditions for 24 hours. After sampling, immediately add 0.2 mL of methanol to stop the reaction.
[0025] Specifically, the CMC@G-nZVI composite material added in the step four includes but is not limited to 0.002g, 0.02g, and 0.2g, the concentration of the PS solution in the step four includes but is not limited to 0, 0.05, 0.15, 0.25, and 0.35 mol / L, the initial pH value of the solution in the step four includes but is not limited to 3, 5, 7, and 9, and the temperature during oscillation under the different temperature conditions includes but is not limited to 15, 25, 35, and 45°C.
[0026] ① CMC@G-nZVI composite material dosage: Under the conditions of temperature of 25℃, pH of 5.5, and PS concentration of 0.35 mol / L, when the dosage of CMC@G-nZVI composite material was 0.02g, the PCB118 degradation rate in the soil of CMC@G-nZVI / PS reaction system was higher than that of the reaction systems with dosages of 0.002g and 0.2g.
[0027] ②PS concentration: When the temperature was 25℃, pH was 5.5, the CMC@G-nZVI dosage was 0.02g, and the PS concentration was 0.35mol / L, the PCB118 degradation rate in the soil of the CMC@G-nZVI / PS reaction system was higher than that of the reaction systems with PS concentrations of 0, 0.05, 0.15, and 0.25mol / L.
[0028] ③ Initial pH value: When the temperature was 25°C, the CMC@G-nZVI dosage was 0.02 g, and the PS concentration was 0.35 mol / L, when the solution pH was 3, the PCB118 degradation rate was higher than that of the reaction systems with pH values of 5, 7, and 9.
[0029] ④ Initial reaction temperature: When the pH value was 5.5, the PS concentration was 0.35 mol / L, the CMC@G-nZVI dosage was 0.02 g, and the reaction temperature was 45°C, the PCB118 degradation rate in the soil of the CMC@G-nZVI / PS reaction system was higher than that of the reaction systems with reaction temperatures of 15, 25, and 35°C.
[0030] Control experiment: Green nano-iron was prepared using plant extract, and the G-nZVI / PS reaction system without modification by adding carboxymethyl cellulose, 2g PCB118-contaminated soil, 2ml deionized water, reacted for 24h at a temperature of 25°C, pH of 5.5, PS concentration of 0.35 mol / L, and a G-nZVI dosage of 0.02g. The PCB118 degradation rate in the soil of the G-nZVI / PS reaction system was the highest, at 26.6% to 30.9%.
[0031] The method for degrading PCB118 in soil by CMC@G-nZVI / PS system is as follows: 2g PCB118-contaminated soil is added with 0.02g CMC@G-nZVI composite material, 2mL deionized water, and 2mL 0.35mol / L PS solution. The initial pH of the solution is 3, and the reaction temperature is 45℃ for 24h. The PCB118 degradation rate is the highest, which is 68.7% to 70.5%.
[0032] Extraction and purification of PCB118 in soil: freeze-dried soil samples after degradation reaction were added with 1:1 acetone / n-hexane solution and ultrasonically extracted 4 times; the combined extracts after extraction were centrifuged, and the supernatant was added with 1 cm anhydrous Na 2 SO 4 , 5cm silicon magnesium adsorbent, 1cm anhydrous Na 2 SO 4 The column was purified by eluting with acetone / n-hexane solution in a volume ratio of 1:9.
[0033] PCB118 determination: PCB118 content was determined by gas chromatography-mass spectrometry. The chromatographic column was SH-1-5S il MS capillary column (30m×0.25mm×0.25μm); the test conditions were: injection port temperature 280℃; ion source temperature 230℃; program temperature was 50℃ for 1min, then 20℃·min -1 The temperature was raised to 280°C at a rate of 100 °C and maintained for 3 min. Splitless injection; injection volume 1 μL; carrier gas was high-purity helium (99.999%), SIM ion scanning mode was selected, and external standard method was used for quantification.
[0034] Calculation of PCB118 degradation rate: The ratio of the difference in PCB118 content before and after the reaction to the initial PCB118 content is used as a method to calculate the degradation rate.
[0035] Table 1 shows the calculated degradation rate of PCB118.
[0036] Table 1 Comparison of PCB118 degradation rates in soils of different reaction systems
[0037]
[0038] The present invention is embodied as follows:
[0039] (1) Preparation of green modified nano-iron
[0040] This method uses ginkgo leaves, which are common in both the north and south of my country, as raw materials, uses its extract to prepare nano-iron, and uses carboxymethyl cellulose to coat and prepare modified nano-iron materials to improve the problems of easy agglomeration and instability of nano-iron in practical applications, while achieving the purpose of green and environmentally friendly experimental materials, experimental processes and products. From the degradation rate comparison table in Table 1, it can be seen that under the same experimental conditions, the degradation rate of PCB118 in the CMC@G-nZVI / PS reaction system is 11.9% to 14.1% higher than that in the G-nZVI / PS reaction system.
[0041] (2) Establishment of degradation reaction method
[0042] This method experimentally analyzed and verified the reaction conditions and methods that affect the degradation efficiency of PCB118 in the CMC@G-nZVI / PS composite system. Factors such as pH value, temperature, persulfate concentration, and activator concentration directly or indirectly affect the sulfate radical (SO 4 ·-) and the speed of the reaction, which has a certain impact on the degradation efficiency of PCB118. Under the experimental conditions and methods, the degradation rate of pentachlorobiphenyl PCB118 in the soil can reach 68.7% to 70.5%, which can effectively degrade and remove PCB118 in the soil, thereby reducing its harm to the ecological environment.
[0043] (3) Economic and environmental protection
[0044] The method of the present invention mainly establishes two procedures through material preparation, reaction conditions and methods, and the required equipment is simple and easy to operate. It has the characteristics of low investment and easy implementation. At the same time, due to the strong free radical activity, polychlorinated biphenyls can be oxidized and degraded into non-toxic small molecular inorganic substances, thereby realizing efficient and environmentally friendly treatment of polychlorinated biphenyls in soil.
[0045] In addition, in the method of the present invention, various waste liquids are collected and subjected to environmental protection treatment such as pH value detection or adjustment before being discharged in compliance with the standards, thus reflecting the purpose of being environmentally friendly.
[0046] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.
[0047] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron, characterized in that: The following steps are involved: Step 1: Preparation of contaminated soil samples: Grind the collected farmland soil without PCBs contamination through a 0.25 mm sieve, add the PCB118 standard solution dissolved in acetone solution to the soil sample, soak it in acetone solution, stir it and place it in a fume hood to dry, and store it for later use. The initial concentration of PCB118 is 9.1 mg / L; Step 2: Preparation of plant extract: Use ginkgo leaves, which are common in both northern and southern my country, to prepare plant extract. Wash the ginkgo leaves with deionized water, air-dry, grind through a 0.25 mm sieve, heat in a water bath at 80°C for 1 h at a concentration ratio of ginkgo leaf powder / deionized water of 36 g / 600 mL, cool to room temperature, and then vacuum filter. The filtrate is the ginkgo leaf extract. Step 3: Preparation of environmentally friendly modified nano-iron: 150 mL of 0.5% carboxymethyl cellulose solution was added dropwise to 150 mL of 0.2 mol / L FeCl3·6H2O solution, mixed, and stirred for 20 min, and then the prepared ginkgo leaf extract was added dropwise to the mixed solution, stirred, and reacted for 30 min. The obtained black suspension was centrifuged at a speed of 8000 r / min for 10 min, the supernatant was discarded, and the mixture was washed with anhydrous ethanol 3 times, washed with deionized water 3 times, and freeze-dried for 24 h. The obtained material is a carboxymethyl cellulose-nano-iron composite material (CMC@G-nZVI); Step 4: Establishment of the PCB118 degradation reaction method in soil: Weigh 2 g of PCB118-contaminated soil and place it in a conical flask, add CMC@G-nZVI composite material to the conical flask, then add 2 mL of deionized water and 2 mL of PS solution, adjust the initial pH value of the solution, seal it, and oscillate (speed of 160 r / min) under different temperature conditions for 24 hours. After sampling, immediately add 0.2 mL of methanol to stop the reaction.
2. The method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron according to claim 1, characterized in that: The CMC@G-nZVI composite material added in step 4 includes but is not limited to 0.002g, 0.02g, and 0.2g. The concentration of the PS solution in step 4 includes but is not limited to 0, 0.05, 0.15, 0.25, and 0.35 mol / L. The initial pH value of the solution in step 4 includes but is not limited to 3, 5, 7, and 9. The temperature during oscillation under different temperature conditions includes but is not limited to 15, 25, 35, and 45°C.
3. The method for degrading PCB118 in soil by activating sodium persulfate with modified nano-iron according to claim 1, characterized in that: The following steps are also included: adding 0.02 g of CMC@G-nZVI composite material, 2 mL of deionized water and 2 mL of 0.35 mol / L PS solution to 2 g of PCB118 contaminated soil, adjusting the initial pH of the solution to 3, and oscillating (at a speed of 160 r / min) for 24 h under the conditions of a reaction temperature of 45°C.
Citation Information
Patent Citations
Method of preparing nanoscale zero-valent iron particles through improved liquid phase reduction method
CN105397106A
Method for improving stabilization efficiency of nanometer zero-valent iron in heavy metal composite polluted soil
CN108246794A
Method for synthesizing nanometer zero-valent iron material from ginkgo leaf extracting solution and application
CN108927530A
Method for modifying synthesisnano zero-valent iron by dispersant and in-situ repairing method
CN109967508A
PH-responsive nano-iron-based sustained-release material, preparation method and application
CN114715994A